A Semiotic analysis of Santos' search for identity in the characters of You Lovely People - Jose, Fiorello R. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1987)
This thesis intended to interpret the symbols employed by Bienvenido Santos in the stories in You Lovely People. The study operated on the interpreted through its Filipino characters and aimed at eliciting the book's underlying theme of the search for national identity. The analysis conducted utilized the Semiotic framework to decipher the author's symbolic personages and use of language. The biplane definition of Ferdinand de Saussure's "sign" is employed in the process of interpretation. It made use of the concepts in semantics in order to elucidate on certain intended meanings in the book. The study is a thematic approach to the stories collected since the compilation runs through the same themes of exile, homelessness, hurt, awareness, and search and preservation of identity. It had viewed these stories collectively as a single book and was collectively analysed. The study, prior to the analysis, has given a biographical account of the author to establish a premise which would later be relevant in the full comprehension of the themes being explored in the book. The brief background of Santos intends to present a broader view of his works as a prose writer. The study concluded that the Filipino characters in the book are symbols of the author's intended meanings. Such meanings are significant of the author's view of life, emotion, sentiments, criticisms and personal search for his Filipino identity.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical reference.